Ethics Of Responsibilities According To Emmanuel Levinas And Its Implications For Interfaith Dialogue: Christian Perspectives - Yohanes Krismantyo Susanta; Yeremia Yordani Putra; Ivan Christian (Jurnal Dialog, 2020)
Based on the literature study, this paper reveals that the ethical concept of Emmanuel Levinas’s responsibility has implications in the context of interfaith dialogue. By carrying out the theory of responsibility, which is based on authentic friendship, interfaith dialogue is not just a formality but is evidently a part of daily life. The results of this study indicate that a human being has never had a single, complete identity. Having known the multifaceted realm of one’s own identity, it seems that we tend to assume that “there are strangers” who dwell within us. Therefore we are invited to treat others as fellow human beings for the sake of God’s pleasure as He is the Creator of this life. Dengan menggunakan studi pustaka, tulisan ini menunjukkan bahwa konsep etika tanggung jawab Emmanuel Levinas memiliki implikasi dalam konteks dialog antaragama. Dengan mengusung teori tanggung jawab yang dilandasi oleh persahabatan yang otentik, dialog antariman tak hanya sekadar formalitas tetapi sungguh-sungguh menjadi bagian dari hidup keseharian. Hasil penelitian ini menunjukkan bahwa seorang tidak pernah memiliki sebuah identitas tunggal di dalam dirinya. Dengan mengakui kemajemukan identitas yang ada pada diri, kita dipanggil untuk mengaku bahwa di dalam diri kita terdapat pula “wajah orang asing.” Itulah sebabnya sebagai pribadi kita diundang untuk memperlakukan “yang lain” sebagai sesama dan memperlakukan orang lain itu seolah-olah kita melakukannya untuk Tuhan, Sang Pencipta.